Konstruksi Makna Pesan Persuasif tentang Pertobatan Ekologis Melalui Media Komunikasi Pastoral Gereja Santa Clara - Yosafhat Christian Limbong; Yesica Yuliani Clara (Journal of Creative Student Research, 2026)
This study aims to understand the construction of meaning of persuasive messages regarding ecological conversion conveyed through the pastoral communication media of Saint Clara Church, North Bekasi Parish, namely the Pastoral Letter, banners, and the Hymn of the Integrity of Creation. A qualitative approach grounded in the socio-psychological tradition and an interpretive paradigm was employed. The Elaboration Likelihood Model (ELM) was used as the analytical framework to examine message processing through central and peripheral routes. Data were collected through in-depth interviews with six parishioners and supported by documentation of the Pastoral Letter, banners, and the hymn. Findings indicate that parishioners demonstrate high levels of motivation and involvement in receiving ecological conversion messages. The central route is reflected through deep reflection on message relevance, argument quality, environmental damage data, and connection to faith. The peripheral route operates through the credibility of bishops and priests, the visual appeal of banners, the emotional influence of the hymn, and the supportive liturgical atmosphere. The construction of meaning formed views ecological conversion as an expression of faith-based responsibility, manifested through concrete daily actions such as reducing plastic use, sorting waste, and conserving energy. The study concludes that pastoral communication integrating cognitive, affective, and conative dimensions can effectively foster ecological awareness and encourage sustainable behavioral change.